Strain-Driven Elemental Re-Distribution during Hydration of the Mid-Lower Crust - Moore, Josephine (Curtin University, 2020)
Fluids are vital for the transport of mass and energy through the Earth’s crust and also for its thermodynamic re-equilibration in response to changes in pressure and temperature. Presented here are observations for the coupling between deformation and reaction, mass transport, and variations in trace-element composition and isotope ratios. Overall, this thesis communicates the importance of mid- to lower crustal deformation for mass transfer and in the attainment of equilibria in the presence of fluid.